Ethnomathematics in Traditional Indonesian Dance: A Systematic Literature Review - Endilina, Euistika; Mariana, Neni; Rahaju, Endah Budi; Purwoko, Budi (Papanda Publisher, 2025)
This study presents a Systematic Literature Review (SLR) on the integration of ethnomathematics in traditional Indonesian dance and its pedagogical potential within mathematics education. Ethnomathematics, as a cultural lens in mathematics, fosters meaningful learning by contextualizing abstract concepts through local knowledge systems. The objective of this review is to explore how traditional dance elements—such as floor patterns, body postures, rhythmic structures, and accessories—reflect mathematical ideas that are adaptable for classroom instruction. A total of ten peer-reviewed articles published between 2014 and 2024 were systematically analyzed based on inclusion criteria involving journal accreditation, mention of mathematical-cultural elements, and instructional integration. Findings indicate that various mathematical concepts, particularly in geometry, arithmetic, and transformation, are embedded in traditional dances like Tari Piring, Topeng Malangan, Gandrung, and Dolalak. These include angles, symmetry, rotation, reflection, coordinate geometry, as well as patterns related to Fibonacci sequences and fractals. The review also reveals the importance of teacher training, curriculum support, and interdisciplinary collaboration in ensuring the effective use of ethnomathematics in classrooms. This research underscores the significance of culturally responsive teaching in the Merdeka Curriculum and highlights traditional dance as a rich and underutilized resource for contextual mathematics learning. Integrating local culture into pedagogy not only enhances student engagement and understanding but also supports the preservation of intangible cultural heritage. However, given that only ten studies met the inclusion criteria over a ten-year span, this review acknowledges that the limited sample may not fully represent all existing research in the field. Further empirical investigations and broader database searches are therefore recommended to strengthen the findings and explore new perspectives on ethnomathematics in traditional arts.